Volumetric absorptive microsampling combined with impact-assisted extraction for hematocrit effect free assays. (December 2017) - Youhnovski, Nikolay; Mayrand-Provencher, Laurence; Bérubé, Eugénie-Raphaëlle; Plomley, Jeff; Montpetit, Hélène; Furtado, Milton; Keyhani, Anahita
Aim: Volumetric absorptive microsampling (VAMS) is a recent technology available for sampling and analyzing low blood volume. The present work describes the utilization of VAMS for the quantitation of naproxen and ritonavir in human blood using a novel bead-based impact-assisted extraction (IAE) procedure.Results: Sampling volume accuracy of the VAMS device was independent of the blood hematocrit (HCT) level, however analyte recovery decreased with increasing HCT when extracted using ultrasonication. In contrast, IAE was unaffected by HCT, resulting in quantitative recovery for all levels evaluated. Precision and accuracy batches, as well as matrix effect evaluation, met acceptance criteria.Conclusion: The IAE procedure coupled with VAMS is immune to HCT biases affecting sampling volume and recovery.